(untitled) (American Journal of Pedagogical and Educational Research, 2023)
This article explores peculiarities of teaching speaking in technical classrooms, the use of various innovative methods in the process of teaching technical terms in foreign language, to improve the communicative competencies and communication skills of students of non-linguistic faculties of the university.